Developing an emotion‐focused therapy model for fear of cancer recurrence: A case‐level task analysis. - Almeida, Susana N.; Elliott, Robert; Silva, Eunice R.; Sales, Célia M. D. (Counselling & Psychotherapy Research, 2024)
Fear of cancer recurrence (FCR) involves anxiety about the possible return or progression of the disease. It is common among people surviving cancer, covering a range of adaptive and maladaptive responses including clinical presentations of FCR, for which different psychological interventions have been developed, most within the cognitive‐behavioural paradigm. Recently, emotion‐focused therapy (EFT) has been proposed as an alternative and has been the subject of research focusing on the cancer population and cancer‐related issues, including FCR. In this study, we looked closely at a successful case from a larger exploratory study, carrying out a discovery‐phase task analysis aimed at identifying the main components of EFT–FCR. We found that this approach generally followed the usual structure of an EFT intervention, with four distinct phases. However, we identified some specific secondary processes (e.g., hypervigilance and catastrophising) and clarified the nature of the core pain in this presentation as existential (e.g., fear of dying).